Is the concordance feature the new black? A workplace study of translators' interaction with translation resources while post-editing TM and MT matches - Kristine Bundgaard; Tina Paulsen Christensen (JoSTrans: The Journal of Specialised Translation)
This paper reports on a workplace study of industrial practices at a large Danish Language Service Provider and is concerned with how seven translators interact with a translation tool when post-editing translation proposals in an environment that combines translation memory (TM) and machine translation (MT). Recently conducted studies indicate that translation resources play a more important role in the translation process than has previously been acknowledged in process research, and those translators who apply computer-aided translation (CAT) tools find the concordance feature particularly useful. This paper investigates which types of translation resources the translators use when translating a technical and a marketing text from English into Danish at their usual workplace, and whether the concordance feature is the translators' first choice of resource. Moreover, the paper analyses how the translators explain their interaction with the concordance feature retrospectively. Based on the results, the paper discusses whether the translators experience this type of interaction as an instance of cognitive friction. The study adopts an embedded mixed method design that combines an experimental and an ethnographically inspired approach. The results show that the concordance search is the translators' preferred resource. Furthermore, the study indicates that, in some cases, concordance searches are instances of cognitive friction in the sense that they disrupt translators' technology-aided cognitive processes. At the same time, the study shows that it is difficult to determine when they are disrupted.